PEMBINAAN YANG DILAKUKAN PIMPINAN DALAM MENINGKATKAN KOMPETENSI USTAZ-USTAZAH PADA LEMBAGA TAHSIN & TAHFIZH QURAN (LT2Q) DAR EL-IMAN PADANG - Mela Kurnia Alnur; Wisroni Wisroni (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
This research was motivated by the success of the Dar El-Iman Tahsin and Tahfizh Quran Institute (LT2Q), this was allegedly due to the guidance from the leadership of the Dar El-Iman Tahsin and Tahfizh Quran Institute (LT2Q) in improving the competence of ustadz. This study aims to see an overview of leadership development in: (1) Improving Cognitive Ability; (2) Developing Affective Ability; (3) Improving Psychomotor Ability.This type of research is descriptive through a quantitative approach. The population in this study were all teachers of Dar El Iman Padang Tahsin and Tahfizh Institute (LT2Q), totaling 37 people. 73% or 27 people were taken as a sample, using the Cluster Random Sampling technique. Techniques for collecting data using questionnaires, through data collection tools in the form of questionnaires. Data analysis techniques use the percentage formula.The research results show that; (1) leadership development in improving the cognitive abilities of religious teachers is categorized as good, (2) leadership development in developing the affective abilities of religious teachers is categorized as good, and (3) leadership development in improving the psychomotor abilities of religious teachers is categorized as very good.Keywords: coaching; Competence of Ustaz and Ustazah